Effects of acute exercise on executive functioning: Testing the moderators. Issue 4 (4th July 2019) - Razon, Selen; Lebeau, Jean-Charles; Basevitch, Itay; Foster, Brian; Akpan, Akanimo; Mason, Justin; Boiangin, Nataniel; Tenenbaum, Gershon
Abstract : Two studies have tested the moderators between acute exercise and executive function gains. In study 1, 60 participants were assigned to 2 groups and performed a handgrip squeezing task at 30% of their maximal voluntary contraction or a stepping task to the cadence of a metronome. Rate of perceived exertions (RPE) and heart rate were measured at 30 s intervals. Trail-making test (TMT) was administered prior to task performance, following RPE = 6 and RPE = 9. In study 2, 83 participants were assigned to 1 of 5 groups. They performed either a handgrip squeezing task or a stepping task up to RPE = 6 or RPE = 9. Participants in the control group have not been engaged in any exercise tasks. Measures of executive function were administered at rest, immediately following exercise tasks, and after 15 min delay. Results from study 1 revealed that both the handgrip squeezing and stepping tasks improved TMT scores after RPE = 9 ( p  < .001). In study 2, executive function scores improved following the handgrip and stepping tasks regardless of the exercise intensity. The control condition resulted in similar results to that of the handgrip and stepping conditions. These findings help delineate the role of moderators in the acute exercise–cognitive gains linkage. Alternative "control" conditions must be tested for broader conclusions and implications.